Assay for determination of daunorubicin in cancer cells with multidrug resistance phenotype - Krumpochova, Petra; Kocurova, Andrea; Dolezel, Petr; Mlejnek, Petr (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2011)
A sensitive assay for direct determination of intracellular level of daunorubicin (DRN) in resistant leukemia cells with overexpressed P-glycoprotein has been developed. This assay is based on a rapid separation of cells from media and fast cut-off of DRN transportation by centrifugation of cells through a layer of silicone oil. Cell pellets were extracted using 1% (v/v) formic acid in 50% (v/v) ethanol in water. The cell extracts were subsequently analysed by liquid chromatography (HPLC) coupled a low-energy collision tandem mass spectrometer equipped with an electrospray ionization source (ESI-CID-MS/MS) operated in the multiple-reaction monitoring (MRM) mode. Calibration curve was linear from 0.4 to 250nM with correlation coefficient (r²) better than 0.998. The limit of quantitation (LOQ) was 0.4 nM. The assay has been successfully applied to a determination of intracellular content of daunorubicin in sensitive K562 and resistant K562/Dox and K562/HHT300 cells.
Keywords: Drug Resistance, Neoplasm; DNA, Neoplasm; mnohočetná léková rezistence; Drug Resistance, Multiple; Linear Models; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; buňky K562; Fluorescence; intracelulární prostor; průtoková cytometrie; Intracellular Space; lineární modely; chronická myeloidní leukemie; Daunorubicin; Antibiotics, Antineoplastic; fluorescence; protinádorová antibiotika; chemorezistence; Sensitivity and Specificity; DNA nádorová; lidé; Humans; K562 Cells; senzitivita a specificita; daunomycin; Flow Cytometry